Pengaruh Model Pembelajaran Snowball Throwing Terintegrasi Konep Deep Learning terhadap Keterampilan Membaca Pemahaman Teks Narasi Murid Kelas III di SDN 4 Sengkol - Maulidian Nadita Iswari; Siti Rohana Hariana Intiana; Mansur Hakim (Mataram University, 2026)
This study aims to determine the effect of the application of the Snowball Throwing learning model integrated with the concept of deep learning on the reading comprehension skills of elementary school students' narrative texts. This study uses a quantitative approach with a quasi-experimental type through a nonequivalent control group design. The subjects of the study were grade III students of SDN 4 Sengkol consisting of an experimental class and a control class. Data collection techniques were carried out through tests (pretest and posttest) and observation. The results of the study showed that there was a significant increase in the reading comprehension skills of students taught using the Snowball Throwing model integrated with Deep Learning compared to conventional learning. This is proven through the results of the t-test which shows that the calculated t value is greater than the t table (3.708 > 2.024) with a significance value of 0.001 < 0.05. In addition, based on the results of the N-Gain test, a value of 0.5513 is obtained which is in the moderate category (G-moderate) with a range of 0.30 ≤ G ≤ 0.70. Thus, the Snowball Throwing learning model integrated with Deep Learning is effective for improving the reading comprehension skills of elementary school students' narrative texts.